The morphologic relationship of the lesser trochanter with the femoral neck and greater trochanter - Akkaya, Mustafa; Gursoy, Safa; Simsek, Mehmet Emin; Isik, Cetin; Acar, Halil Ibrahim; Bozkurt, Murat (International Journal of Research in Medical Sciences, 2019)
Background: The anatomy of the proximal femur comprises important landmarks for many orthopedic surgical procedures. However, this area exhibits morphological differences depending on race, gender and age. Besides being the insertion area of the hip flexor muscles, the lesser trochanter is also used as an angular reference in many orthopedic surgical procedures. The aim of this study is to investigate the morphologic relationship of the lesser trochanter with the femoral neck and greater trochanter. Methods: Around 67 dry femur bones (32 left, 35 right) belonging to humans of unknown gender that belong to the Ankara University Medical Faculty, Department of Anatomy were used in this study. The morphologic relationship of the lesser trochanter (TRMI) with the femoral neck (FN) and greater trochanter (TRMJ) was studied and the results were provided in a table. Results: The measured mean lesser trochanter and greater trochanter tip distance was 67.5±4.9mm (60mm-75mm). The angle between the tip of the lesser trochanter and the center of the femoral neck was measured as 35.050±5.060 (290-420) degrees. The distance between the tip of the lesser trochanter and the center of the femoral neck was measured as 15±2.8mm (10mm-20mm). Conclusions: In addition to the angular relationship of the lesser trochanter with the femoral neck, its relationship in terms of distance with the greater trochanter and femoral neck are the anatomic relationships that are noteworthy for the lesser trochanter, which is used as a landmark during orthopedic surgical procedures.